Analysis of skeletal pain, general symptoms and patient-reported outcome measures and their value in detecting symptomatic progression – An interdisciplinary prospective study in patients with multiple myeloma - Carlotta Pietsch; Monika Engelhardt; Gabriele Ihorst; Laura Wystrach; Johannes Jung; Hagen Schmal; Andreas Frodl; Ralph Wäsch; Evangelos Terpos; Georg W. Herget (Journal of Bone Oncology)
Delayed diagnosis of multiple myeloma (MM) and progressive disease (PD) can both increase the risk of skeletal complications and do affects patients’ quality of life (QoL). In this prospective study we analyzed skeletal pain, general symptoms and patient-reported outcome measures (PROMs) in patients with MM and their value in detecting symptomatic progression.We evaluated 502 patients, 47 with initial diagnosis (ID) of MM and 455 follow-up patients. At ID, 74% reported bone pain, mostly in the spine. General symptoms, particularly fatigue, were present in 89% of the patients. 88/455 (19%) of the follow-up patients experienced PD. Of these, 65% reported skeletal pain and 81% exhibited general symptoms, with fatigue being the most common. PD was suspected and confirmed as the cause of clinical symptoms in 59/88 (67%) and not suspected in 29/88 (33%). Occurrence and character of bone pain and general symptoms differed significantly between patients with and without PD, as did QoL and health-related status. Logistic regression analysis demonstrated that bone pain at night, pain in various locations, pain of known character with occurrence in different location, pain in the chest, pelvis, and thigh as well as fatigue and weight loss were associated with an increased risk of PD.In conclusion, bone pain and general symptoms are helpful in identifying both MM and PD. PROMs can aid in the diagnosis of PD through symptom-based patient assessment. Serologic and, especially in the case of skeletal complaints, additional radiologic diagnostics are required to confirm suspected and to detect unexpected PD.